Pengaruh Likuiditas Dan Profitabilitas Terhadap Financial Distress Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016 - Syamsul Bakhri; erna listyaningsih; Nurbaiti Nurbaiti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2012)
Abstract, This study aims to determine the effect on Financial Distress. Independent variables in thisresearch are Liquidity (X1), Profitability (X2),.While the dependent variable is the Financial Distresson the transportation company in Indonesia Stock Exchange period 2014-2016. Sample amounted to19 companies. The analysis was done by processing data using SPSS version 24 which was run withcomputer media. Based on the results of the research that has been done, it is found that Liquidity andProfitability significantly affect the Financial Distress on transfortasi company in Indonesia StockExchange period 2014-2016. While the test results f is Fcount> Ftable, it means there is asimultaneous or joint influence between Liquidity and Profitability to Financial Distrss on transfortasicompany in Indonesia Stock Exchange Period 2014-2016.